Lo fantástico en la narrativa de Julio Ramón Ribeyro - Castillo Contreras, Diego Gianfranco (2018)
The twentieth century of Peruvian literature was full of great changes as a result of the socio-economic conflicts resulting from Odria's coup producing a great change in our literature that until then had as its main axis the indigenismo with its top representatives Ciro Alegría and José María Arguedas._x000D_ Later, in the 50s, Peruvian literature represented by great writers such as: Enrique Congrains, Oswaldo Reynoso, Sebastián Salazar Bondy, Julio Ramón Ribeyro among others; They were also subjected to these changes: modernism, the rural exodus and the development of the middle class, beginning the fantastic narrative of Julio Ramón Ribeyro, which is composed of a small group of stories, perhaps because of this it has been little studied by the Peruvian and foreign literary criticism that has preferred to analyze their realistic stories.